Parâmetros biomecânicos e percepção de hemiparéticos crônicos com o uso de dispositivos auxiliares na marcha - Janaine Cunha Polese (2011)
The acquisition of independent gait is the primary goal of rehabilitation programs for post-stroke individuals. In this sense, the prescription of walking sticks (WS) aims to assist gait restoration, since these devices may increase stability and balance. However, there is no consensus regarding the effects of WS on gait biomechanics of chronic stroke survivors, nor about the perceptions of the individuals regarding their use. Therefore, the objectives of this study were to investigate how the use of WS (canes or crutches) affected the kinematics and kinetics of gait for subjects with chronic stroke after their walking has been stabilized, when walking at their comfortable and fast speeds, as well as to assess their perceptions regarding the use of these devices. The gait biomechanics of 19 chronic stroke survivors with a mean age of 56.5 years, was evaluated using the QualiSys motion analysis system and a synchronized force plate during four experimental conditions: (i) with WS at comfortable speeds; (ii) with WS at fast speeds; (iii) without WS at comfortable speeds; and (iv) without WS at fast speeds. The biomechanical outcome variables included speed, angular kinematics, as well as the power and work of the hip, knee and ankle joints in the saggital plane. To assess the individuals perceptions regarding WS use, a standardized questionnaire with five questions scored on a Likert scale was applied to 23 chronic stroke survivors, with a mean age of 58.4 years. ANOVAs (2X2) with repeated measures were used to investigate the main and interaction effects between the WS (with and without) and speed (comfortable and fast) conditions. To assess whether the observed frequencies differed from those expected in the questionnaire items, Chi-square tests were employed. The results demonstrated that increases in speed were associated with the use of WS in both conditions, at fast (F=23.49, p<0.0001) and comfortable speeds (F=16.09, p=0.001). No statistically significant differences were found for any of the kinematic parameters (0.39<F<1.43; 0.24<p<0.54). The ANOVAs revealed significant main effects of the WS, indicating increases in power generation of the ankle plantar flexors (F=8.69, p<0.01, power=0.81), hip flexors (F=15.75, p<0.01, power=0.97), and knee extensors (F=19.30, p<0.01, power=0.99). No differences were observed for hip extension power generation (F=0.34, p=0.56) and the knee power absorption phases (0.08<F<0.05, 0.82<p<0.93). In addition, no interactions were found (0.003<F<1.35; 0.26<p<0.96) for all the investigated variables. The results of the Chi-square tests